Ray-tracing Simulations and Spectral Models of X-Ray Radiation in Dusty Media - Claudio Ricci; Stéphane Paltani (The Astrophysical Journal, 2023)
Dust can play an important role in shaping the X-ray spectra and images of astrophysical sources. In this work we report on the implementation of dust in the ray-tracing platform RefleX . We illustrate the different effects associated with the interaction between X-ray photons and dust grains, such as dust scattering, near-edge X-ray absorption fine structures, and shielding. We show how the cross sections of the photon–gas interaction change depending on the fraction of metals in dust grains (i.e., the dust depletion factor). We compare RefleX simulations to the most widely used absorption model that includes dust and show how X-ray spectra are affected by the presence of dust in the absorbing/reprocessing medium for different geometries. We also show how RefleX can be used to reproduce the dust scattering halos observed in Galactic sources, and we release the first torus X-ray spectral model that considers dust absorption and scattering ( RXTorusD ), to reproduce the spectra of active galactic nuclei (AGNs). RXTorusD also considers other physical processes that are not included in the most widely used AGN torus models, such as Rayleigh scattering and scattering on molecular gas, which can lead to remarkable differences in the predicted X-ray spectra for the same set of geometrical and physical parameters.